HANDLING OF ROHINGYA REFUGEES IN INDONESIA AS A TRANSIT COUNTRY - Puspita, Rona; Nofli (Indonesian Law Journal, 2024)
Indonesia has long been a transit location for many refugees, including those from the Second Indochina War, especially Vietnam and Cambodia, who began entering Indonesian territory in 1975. Currently, refugees from Myanmar, namely the Rohingya, are starting to enter Indonesia because their country is experiencing a civil war conflict in which prolonged. As a transit destination country, Indonesia cannot refuse them because of international conventions that the government complies with, but as time goes by Indonesia experiences overcapacity in refugee matters and the final destination country does not immediately make a decision regarding the fate of these refugees. So there is a need for assistance and solutions from the Indonesian government regarding this matter refugees. The aim of this research is to analyze in depth the refugee phenomenon in Indonesia and provide solutions related to this problem through an academic perspective. The research method is a sociolegal approach regarding legal policies regarding refugees in Indonesia. The results of the research are that there are several steps that need to be taken refugees, including reactivating islands in Indonesia as transit locations past experiences during the Vietnam war, efforts to ratify the convention on refugees because Indonesia is not a signatory country, then clarifying the presidential regulation on refugees so that its implementation is clearer.